Construction of a proteolysis-resistant peptide sequence of the food recombinant protein GDF-11 and plasmid synthesis for its expression in E. coli - Valieva, Sh. S.; Tikhonov, S. L.; Tikhonova, N. V.; Timofeeva, M. S.; Shikhalev, S. V. (Vestnik MGTU, 2025)
The GDF-11 protein has a positive effect on animals and humans in inflammatory and infectious processes, regeneration and rejuvenation, its high expression is observed in many organs and tissues. The relevance of the problem of oral use of many proteins and peptides, including the GDF-11 protein, as drugs and in specialized and functional products is noted. The aim of the research is to develop a proteolysis-resistant peptide sequence of the GDF-11 protein with virtual screening of its toxicity, allergenicity, uniqueness with subsequent synthesis of the corresponding plasmid for protein expression in E. coli. The GDF-11 protein, pET-25b(+) plasmids for expression in E. coli with the peptide sequence CTVDСFFECAFGСWDС have been used as objects of study. The GDF-11 protein gene with the sequence CTVDСFFECAFGСWDС has been synthesized from oligonucleotides using the cyclic assembly method. The obtained plasmid sequence encoding the new GDF-11 protein has been treated with restriction endonucleases BamHI and XhoI and cloned into the pET-25b(+) vector for E. coli expression. The clones have been sequenced by the Sanger method. The distribution and identification of primers in the obtained sequence have been studied by the MALDI-TOF MS Ultraflex method. A new unique peptide sequence CTVDСFFECAFGСWDС with cyclization at the C1-C4, C1-C2, C1-C3 bonds of the GDF-11 protein is developed, which allows increasing its resistance to proteolysis and, accordingly, opens up the possibility of oral use in prophylactic food products. Based on virtual screening, it is established that the new peptide chain CTVDСFFECAFGСWDС of the GDF-11 protein is not toxic to the cardiovascular and nervous systems, is not hepatotoxic, does not have cytotoxicity, does not have allergenicity and is characterized by high plasma clearance and an average half-life.